Metaphoric Speculation: Rereading Book 15 of Augustine's De Trinitate - McClellan, Emeline (Augustinian studies, 2021)
This article argues that De trinitate advocates a process of "reading" God through metaphor. For Augustine, as for Plotinus, human beings understand God (to the degree that this is possible) not by analyzing him rationally but by seeing him through the metaphor of the human mind. But unlike Plotinus, Augustine claims that the imago dei, with its triadic structure of memory, understanding, and will, serves as metaphor only to the extent that it experiences Christ's redemptive illumination. The act of metaphor is a kind of interior "reading" during which the mind reads the imago dei as a mental text, interprets this text through Christ's aid, and is simultaneously transformed into a better image.